A core–shell nanoparticle–peptide@metal–organic framework as pH and enzyme dual-recognition switch for stepwise-responsive imaging in living cells. Issue 66 (31st July 2018) - Shen, Hong; Liu, Jintong; Lei, Jianping; Ju, Huangxian
Abstract : A stepwise-responsive strategy was achieved based on a core–shell nanoparticle–peptide@metal–organic framework for imaging lysosomal cathepsin B. Abstract : A core–shell nanostructure is fabricated with a pH-sensitive metal–organic framework shell and a peptide functionalized gold nanoparticle core via a mild synthetic route. The nanostructure can be applied as a dual-recognition switch in response to an acidic environment and enzyme activity, sequentially, leading to a stepwise-responsive strategy for imaging lysosomal cathepsin B.